Avaliação do impacto das mudanças climáticas na oferta hídrica da bacia hidrográfica do reservatório Óros usando os modelos de mudanças climáticas do IPCC-AR4, levando em consideração as diversas incertezas associadas - Fernandes, Wescley de Sousa (2012)
In the present work flow projections for the basin Óros (Ceará) were obtained using the precipitation of global models of the fourth report of the Intergovernmental Panel on Climate Change (IPCC-AR4) for the period 2010 to 2099 the A1B scenario. The flows were generated by the hydrologic model Soil Moisture Account Procedure (SMAP). To obtain these, the precipitations were statistically corrected from the observed data, considering the distributions of the type series range. The evaporation model input rainfall-runoff were two considerations, the first consideration obtained by using flow hydrologic model initialized with SMAP evaporation provided by INMET and considers that the second boot occur by evaporation estimated by the method of Penann Mothieth. For the analysis of interannual variations were observed the characteristics of trends of the series (using the classical method of Mann-Kendall-Sen), the changing patterns of variation (analysis of the mean and coefficient of variation of the series) and the analysis of extremes (compared cumulative distribution curves of the twentieth century and XXI). For seasonal analysis considered the climate anomaly in the middle of the XXI century models over the twentieth century. For analysis it was observed that interannual hydrologic model initialization SMAP with evaporation estimated by the modified Penann Motheith can arise as an implementation for the hypothesis test of Mann Kendall Sen. The calculation of the coefficient of variation showed that despite the short confrontation over the occurrence of variability, in the case of streamflow series obtained by SMAP initialized with estimated evaporation, the rounds of the models MIROC3_2_MEDRES reported increases in variability for the XXI century in relation to the twentieth century. When booting into SMAP occurs through evaporation provided by INMET is a great diversification in the values of variability. Although the interannual analysis, the curve of cumulative distribution function (CDF) showed that eight of the analyzed models (models initialized with evaporation estimated by the method of Penann Motheith-modified) 3 have a higher frequency of dry events, have a third event frequency wet and two models showing no meaningful analyzes approaching the curve generated by the series of observed flows. As for seasonal analysis of the flow is observed that when using the method of Penann Motheith modified to evaporation (initialization SMAP) values of flow rates become smaller than the values obtained by series generated by the hydrologic model initialized with evaporation provided by INMET , relating the new century, the twentieth century.